2017
DOI: 10.1017/s1041610217001508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the lived experiences of family caregivers of patients with dementia and of patients with cancer in Indonesia

Abstract: Background:Dementia, even more than cancer, demands long-term care. While in Indonesia cancer is accepted as a disease requiring caregiving, dementia is still considered "a normal condition." These differences might affect the experiences of caregivers, especially those relating to social health, the subject of our study. We aim to describe and compare the lived experiences of family caregivers of patients with cancer (PWC) with those of patients with dementia (PWD) in Yogyakarta, Indonesia, and to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
3
25
1
4
Order By: Relevance
“…34,35,42 In fact, our previous study in Indonesia showed that financial challenges of caregivers of patients with cancer were greater than those of caregivers of patients with dementia. 43 Our study also confirms previous findings that providing care can also have indirect negative financial consequences, such as a reduction of the caregiver’s time spent at work or at other productive tasks. 35…”
Section: Discussionsupporting
confidence: 91%
“…34,35,42 In fact, our previous study in Indonesia showed that financial challenges of caregivers of patients with cancer were greater than those of caregivers of patients with dementia. 43 Our study also confirms previous findings that providing care can also have indirect negative financial consequences, such as a reduction of the caregiver’s time spent at work or at other productive tasks. 35…”
Section: Discussionsupporting
confidence: 91%
“…11 These have highlighted various lived experiences, each of which offer difference experiences dependent on the disease state of individuals. Whilst these are recurrent themes such as constant burden, 8,10 knowledge 9,11 and role reversal, 11 there are also differences related to reward, worth and pleasure which have been associated with caregiving for people with terminal illness, 12,13 but also fear and concern regarding harm, associated with caregiving for people with cognitive impairment. 14,15 Various sociological models have been developed to explain caregiver-care recipient dyads.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps because dementia has no cure, this sense of fear and hopelessness continues to influence the care offered to people with dementia in Western countries. In other countries, by contrast, dementia is accepted as a normal condition of ageing and affected people are encouraged to engage and remain in their community 7 . Such cultural variations contribute to large geographical discrepancies in dementia treatment and care.…”
Section: [H1] Introductionmentioning
confidence: 99%